2023
DOI: 10.1039/d3bm00132f
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of polyvinyl pyrrolidone-K90/Eudragit RL100-based dissolving microneedle patches loaded with alpha-arbutin and resveratrol for skin depigmentation

Abstract: Alpha-arbutin (AA) and resveratrol (Res) are widely used in skin-lightening products. However, current topical formulations have minimal skin-lightening effects due to low absorption and poor solubility of these active compounds....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Due to the low absorption and poor solubility of resveratrol, studies have also been conducted to increase the bioavailability of this compound through the use of dissolving microneedle patches. Both in vitro and in vivo studies revealed that the use of these patches effectively improved intradermal resveratrol delivery compared to a cream formulation; therefore, it can be concluded that this approach is a promising way for the effective local delivery of whitening ingredients in the melasma treatment [139].…”
Section: Musa Sapientum Rejected Unripe Fruit Extractsmentioning
confidence: 99%
“…Due to the low absorption and poor solubility of resveratrol, studies have also been conducted to increase the bioavailability of this compound through the use of dissolving microneedle patches. Both in vitro and in vivo studies revealed that the use of these patches effectively improved intradermal resveratrol delivery compared to a cream formulation; therefore, it can be concluded that this approach is a promising way for the effective local delivery of whitening ingredients in the melasma treatment [139].…”
Section: Musa Sapientum Rejected Unripe Fruit Extractsmentioning
confidence: 99%
“…Additionally, the dose reduction index (DRI) was calculated as the ratio of the dose of each drug used in combination with the dose of that drug when administered alone to achieve the same Fa level. A DRI value > 1 suggests that the dose of the drug can be reduced in combination therapy without compromising the desired therapeutic effect [50].…”
Section: Analysis Of Dual Therapy By Compusyn Softwarementioning
confidence: 99%